Long‐term vegetation responses to different goat grazing regimes in semi‐natural ecosystems: a case study in Tenerife (Canary Islands). Issue 1 (14th June 2012) - Fernández‐Lugo, Silvia; Arévalo, José Ramón; de, Lea; Mata, Javier; Bermejo, Luis Alberto; Prober, Suzanne
Abstract Question How are semi‐natural ecosystems affected by goat grazing regime (heavy, light and long‐term abandonment)? Location Anaga Rural Park, Tenerife Island, Canary Islands (Spain). Methods We evaluated plant species composition, diversity and structure (frequencies of functional groups based on growth form and bare ground) for three goat grazing regimes using 63 permanent point‐quadrat transects. The effect of orientation (N vs S slope) was also analysed. Data were collected in the spring during each year from 2001 to 2005. Results Grazing regime affected the studied functional groups differently. The frequency of annual grasses was higher in the heavily grazed areas, shrubs decreased sharply from abandoned to heavily grazed areas, and shrub legumes appeared less abundant in the lightly grazed transects. An interaction between grazing regime and orientation affected some functional groups. Grazing led to higher plant diversity, and did not affect the frequency of bare ground or native and endemic species. There were no strong differences in species composition among the three grazing regimes. However, species composition in abandoned areas was characterized by a higher abundance of late‐successional and endemic shrub species, while herbaceous species typical of pastures were more common in the grazed areas. Conclusions Grazing regimes noticeably affect the composition and structure of the vegetation of semi‐natural ecosystems but do not result in a complete turnover in species composition. Goat grazing is beneficial for maintaining traditional open agroecosystems; however, controlling the grazing intensity can avoid negative effects on the vegetation, particularly the sharp reduction in shrub and palatable species. Some abandoned areas should be maintained to preserve grazing‐sensitive endemic shrub species in these Canarian semi‐natural ecosystems.